Miskawayh’s philosophy of history in the light of Tajarib al-Umam - Azmul Fahimi Kamaruzaman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This writing seeks to discuss and interpret Miskawayh’s philosophy of history as may be perceived in the section on contemporary history of the Tajarib al-Umam that tell the history of Buyid era in his work. As a historian of medieval Islam, Miskawayh did not clearly expound his philosophy of history in the works of Tajarib al-Umam. Employing textual interpretation and analysis method comprehensively and partially, this writing seeks to construct Miskawayh’s philosophy of history in the light of Tajarib al-Umam. The results of this analysis and interpretation show that the section on Miskawayh’s contemporary history is considered important for the philosophy of history as constructed by Miskawayh. There are three forms of historical development and stages in the section, i.e. formation and stability, weakness and restoration apart from brilliant achievement. These three forms and stages characterise the semi-cyclical concept history in Miskawayh’s philosophy of history. This concept indicates that Miskawayh was among the earlier Muslim historian who pioneered the cyclical form of philosophy of history and he thus preceded other Muslim historians such as Ibn Khaldun.